ESQ Pemoderasi Pengaruh Faktor Internal pada Perilaku Disfungsional Auditor - Sari Wulan, Ni Putu Ayu Nikita (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p15, 2024)
This research aims to provide empirical evidence of the influence of Machiavellian traits and experience on auditors' dysfunctional behavior with ESQ (Emotional Spiritual Quotient) as a moderator. The population of this research is 866 auditors who work at Public Accounting Firms in the Provinces of Bali and East Java. The sample was determined using a purposive sampling technique with data collection using a questionnaire technique. The data analysis used is Partial Least Square (PLS). PLS is a Structural Equation Modeling (SEM) model which is based on components or variants. The research results prove that Machiavellian traits have a positive effect on auditors' dysfunctional behavior, but experience has no effect on auditors' dysfunctional behavior. This research also proves that ESQ is able to weaken the influence of Machiavellian traits on auditors' dysfunctional behavior, but ESQ is unable to moderate the influence of experience on auditors' dysfunctional behavior. The results of this research support attribution theory and the theory of attitude change. Keywords: Machiavellian Characteristic; Experience; Dysfunctional Auditor Behavior; ESQ